Passiflora cana, a New Species of Passiflora Section Decaloba (Passifloraceae) from Peru - Macdougal, John M.; Esquerre-Ibañez, Boris (Phytotaxa, 2025)
Passiflora cana, a new species of Passiflora (Passifloraceae) endemic to the mountain forests in Amazonas and Cajamarca Departments, Northern Peru, is described and illustrated from herbarium and living material. The species has bilobed leaves and is notable for its dense white pubescence throughout and green-centered white flowers. It is compared to similar species and placed in subgenus Decaloba section Decaloba.